2022
DOI: 10.3390/biology11081138
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Divergence of the Sex-Linked Region between Two Wild Spinach Progenitors, Spinacia turkestanica and Spinacia tetrandra

Abstract: The sex-linked region (SLR) plays an important role in determining the sex of a plant. The SLR of the Y chromosome, composed of a 14.1-Mb inversion and a 10-Mb Y-duplication region (YDR), was deciphered in Spinacia oleracea previously. However, our understanding of the SLR in its wild relatives, S. turkestanica and S. tetrandra, remains limited. In this study, we used 63 resequencing data from the three Spinacia species to infer the evolution of the SLR among the Spinacia species. In the SLR, all the cultivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…S. oleracea L. subsp. turkestanica also shared a similar sex‐linked region (SLR) with S. oleracea (She et al ., 2022). These may be because S. oleracea L. subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. oleracea L. subsp. turkestanica also shared a similar sex‐linked region (SLR) with S. oleracea (She et al ., 2022). These may be because S. oleracea L. subsp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sex chromosome pairs in the part of S. tetrandra accessions are heteromorphic. In 2022, She et al . reported that S. oleracea shared a similar sex‐linked region with S. oleracea L. subsp.…”
Section: Introductionmentioning
confidence: 99%
“…S. turkestanica is the closest wild relative of S. oleracea , and these species share a similar SLR on chromosome 4 (She et al, 2022b). We used synteny analysis to describe the S. turkestanica SLR in detail.…”
Section: Main Textmentioning
confidence: 99%
“…We found orthologs of 35 S. oleracea YDR genes in the S. tetrandra assembly, but they are scattered across the genome (Supplementary Table 4), consistent with the previous conclusion that most S. oleracea YDR genes were recently translocated into the region (She et al, 2023). We previously described complete male-specificity of the YY_141140.1 gene (coding sequence length: 414 bp) within the YDRs of both S. oleracea and S. turkestanica (She et al, 2022b). A phylogenetic tree of YY_141140.1 and its orthologs shows that the relationships of the four outgroup species do not correspond with the species tree (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The single gene systems that have recently been discovered (Akagi et al, 2014;Muller et al, 2020), including new ones generated by sex chromosome turnovers (Vicoso, 2019), will not be selected for changed recombination (reviewed in Charlesworth & Harkess, 2024). Moreover, Y-and X-linked regions can also arise if sex-determining mutations arise within a recombinationally inactive region (Charlesworth, 2019) and examples of sex-linked regions (SLRs), within pericentromeric regions are now known in several plants (Zhou et al, 2018;Rifkin et al, 2021;She et al, 2023;Yue et al, 2023).…”
Section: Introductionmentioning
confidence: 99%